2021
DOI: 10.3389/fmolb.2021.742023
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Pseudomonas Quinolone Signal Forms Chiral Supramolecular Assemblies With the Host Defense Peptide LL-37

Abstract: Host defense antimicrobial peptides (HDPs) constitute an integral component of the innate immune system having nonspecific activity against a broad spectrum of microorganisms. They also have diverse biological functions in wound healing, angiogenesis, and immunomodulation, where it has also been demonstrated that they have a high affinity to interact with human lipid signaling molecules. Within bacterial biofilms, quorum sensing (QS), the vital bacterial cell-to-cell communication system, is maintained by simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The 1-GLFD assembly formation can be most efficiently tracked by CD spectroscopy due to the chiral intermolecular exciton coupling between the respective π–π* transitions of the spiropyran chromophores. ICD signals can arise from both chiral and achiral molecules, including spiro compounds, where the packing results in a chiral supramolecular assembly such as for H-type or J-type aggregates . The packing of 1-GLFD molecules is likely such that the spiropyran units are positioned close to each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1-GLFD assembly formation can be most efficiently tracked by CD spectroscopy due to the chiral intermolecular exciton coupling between the respective π–π* transitions of the spiropyran chromophores. ICD signals can arise from both chiral and achiral molecules, including spiro compounds, where the packing results in a chiral supramolecular assembly such as for H-type or J-type aggregates . The packing of 1-GLFD molecules is likely such that the spiropyran units are positioned close to each other.…”
Section: Resultsmentioning
confidence: 99%
“…Inversely, the attenuation of specific fusion activity is also important as in the case of viral entry, where inhibitory membrane-active peptides, e.g., in the drug Fuzeon, demonstrate the potential of peptides interfering with membrane processes. As a natural inspiring example where peptidic self-assembly plays a key role in membrane manipulation, antimicrobial peptides often form temporary, assembled constructs that could be highly relevant for exerting toxicity on targets or for modulating other related biological functions. Recently, it has also been indicated that the manipulation of their membrane activity and thus their antimicrobial affinity can also be achieved by the formation of functional supramolecular coassemblies. ,, However, these constructs often adopt only partially ordered assemblies, which limits their controlled use as functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…The natural peptide interaction with mammalian EVs at these locations could aid cargo redistribution, whereas more membrane disrupting AMPs could disrupt EVs and release cytosolic components that are relevant for wound healing. On the other hand it is likely, that tethering bacterial EVs, which carry important components, such as compounds of quorum sensing, could be also relevant for exerting AMP antibiofilm activity (Hancock et al., 2021 ; Zsila et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…D-and L-LL-37 significantly downregulated the expression of the Rhl QS-related genes rhlA and rhlB in P. aeruginosa, inhibited the synthesis of rhamnosyltransferase, reduced biofilm formation, and degraded an existing P. aeruginosa biofilm [142]. LL-37 can also form supramolecular associations with Pseudomonas quinolone signal (PQS) molecules, another important component of the QS regulatory network of P. aeruginosa, and the QS signal molecules captured by the peptides are sequestered in coassemblies, thus helping to prevent and eradicate bacterial infection [143]. Gj-CATH2 has strong bactericidal and antibiofilm effects on Streptococcus mutans.…”
Section: Amps Acting On Biofilmsmentioning
confidence: 99%